Sentymentalna autokreacja Augusta Kotzebuego w Pamiętniku ze zsyłki na Syberię - Sobina, Iga (Tematy i Konteksty, 2011)
The article Sentimental Autocreation of August Kotzebue in his Memoirs from Siberian Deportation provides a presentation of problems discussed in the unknown to scholars text by the German playwright. The autobiographical work was written in the town of Kurgan where Kotzebue served the sentence of deportation for an unknown offence against Tzar Paul I of Russia. The description of the unusual year 1801 is provided in two rhetoric dimensions. The first one serves the purpose of presenting the author as a warm-hearted and sensitive man. Such stilization, inspired by the pattern of sentimental novels, is considered as the registry of emotional states of a frightened, desperate and afflicted by illnesses prisoner who wanders the vastness of Siberian plains without any reason known. The other rhetoric dimension is considered as the objective version of description of reality and thus it provides its reader with information of ruthlessness of tzar reprisal system. The diary is a testimony of a human being facing the nature of fierce Syberia. This helpless and downgraded person gradually becames dehumanized. Finally, the memoirs also provide many rare information about the closest entourage of Tzar Paul I.